Unspeakable and Unspoken: Gender Inequalities in the Labor Experience of Female Social Scientists in Chile - Lube Guizardi, Menara (2025)
The article discusses the results of a qualitative study on how gender inequality is experienced by female social scientists in their relationship with their male colleagues and/or authorities in Chilean universities. It aims to establish a typology of the axes in which these inequalities are manifested and/or reproduced. After synthesizing an overview of the studies and statistics on gender inequalities in Chilean academia, we present the qualitative methodology of the study, based on the in-depth interviews with fifty women working as researchers and/or professors at twelve universities in nine cities of the north, center, and south of Chile. Then, we delve into the qualitative analysis and discuss the three axes of gender inequality identified in the women’s accounts and their intersectional dimensions: (i) the salary gaps and work overload of women compared to men; (ii) the little recognition of women’s skills and careers; and (iii) the assumption that research and leadership are masculine areas. In the final remarks, we summarize the conclusions of the study, addressing how the multidimensional and multifaceted nature of sexist experiences in university environments generates a relational “atmosphere” in which the boundary between inequalities and violence is blurred.